RECEIVING OF THE PREDETERMINED MECHANICAL CHARACTERISTICS OF STEEL 35 L BY MEANS OF FORMING OF THE OPTIMAL STRUCTURE AT THE STAGE OF CRYSTALLIZATION - V. M. Gatsuro; L. V. Shvetsov (Литьë и металлургия)
There is shown, that influences of silicon-free complex foundry allow о the processes of crystallization of carbon steel 35L have essentially changed the mechanical and foundry properties of steel, that allows to offer the replacement of steel allows by carbon steels without reduction of durability of the prodused from them details.